Short Term Versus Long Term Graft Uptake Rates Following Myringoplasty in Chronic Otitis Media–Mucosal Type - Acharya, Kunjan (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: The objective of study is to compare overall success rate of myringoplasty after 6 weeks and 4 months following surgery. Materials and Methods: Retrospective analytical study was done at Lahan Ear Hospital, Nepal. All the data were collected from the operative notes of Lahan ear hospital which were done in-between August 2010 to October 2012 for a period of 26 months. All Myringoplasty were done under local anesthesia using either temporalis fascia or Tragal cartilage. Outcome measured was the graft uptake rate at the end of 6 weeks and end of 4 months. Results: Total of 978 patient underwent Myringoplasty during the period of 26 months. The mean age was 24.4 years, minimum age who underwent surgery was 15 years and maximum age was 60 years. 571 patients completed 6 weeks follow up and only 419 patient completed 4 months follow up. The overall graft uptake rate was 82 % and 78 % by the end of 6 weeks and 4 months respectively. Conclusion: The overall graft uptake rate was 82 % by the end of 6 weeks which further decreased to 78% by the end of 4 months. Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015